RETRACTED: A 1 year course of starch- and sucrose-reduced diet used by irritable bowel syndrome patients with diarrhoea and the effect of genetic variants - Garcia-Etxebarria, Koldo; Gayoso, Lucía; Arzallus, Teresa; Montalvo, Isabel; Lizasoain, Jacobo; Izagirre, Arantzazu; Ezkurra, Ander; D’Amato, Mauro; Etxeberria, Usune; Bujanda, Luis (Frontiers in Nutrition, 2023)
Background Irritable bowel syndrome is a heterogeneous syndrome and it is difficult to find an effective treatment. Previously, a starch- and sucrose-reduced diet (SSRD) demonstrated promising short-term outcomes. It was proposed that genetic variants in the sucrose-isomaltase gene might influence this success. Our aim in this work was to extend the follow-up study to 1 year and to analyse the effect of the genetic variants of genes involved in starch and sucrose metabolism. Methods IBS-SSS questionnaire, IBS-QoL questionnaire and questionnaires about adherence, difficulty and food assessment were sent to 34 patients after 6 months and 1 year after the end of the dietary intervention. In addition, 11 genes involved in sucrose and starch metabolism were sequenced. Results Twenty-three participants responded to the 6 months follow-up and 16 to the 1 year follow-up. IBS-SSS total value increased 59.71% in the 6 months follow-up compared with the end of the intervention (p = 0.0018), and 55.39% in the 1 year follow-up (p = 0.0166); while IBS-QoL score decreased 24.09% (p = 0.0002) and 18.07% (p = 0.0022), respectively. The adherence decreased by 29.11% (p = 4.8 × 10−5) and 27.21% (p = 0.0054), respectively. In addition, carriers of pathogenic variants on the SI gene showed a slightly better performance than non-carriers. Finally, the participants showed less satisfaction over time with 18 allowed foods in the diet. Conclusion Over time the SSRD is difficult to follow and the genotype might affect the performance of the diet. Since this diet could be a promising therapeutic option, a larger cohort needs to be analysed to validate the results and to compare it with other diets.